"Often Relatives are the Key […]" –Family Involvement in Treatment Decision Making in Patients with Advanced Cancer Near the End of Life. (26th October 2020) - Laryionava, Katsiaryna; Hauke, Daniela; Heußner, Pia; Hiddemann, Wolfgang; Winkler, Eva C.
Abstract: Background: Family communication has been increasingly recognized as an important factor in decision making near the end of life. However, the role of the family in decision making is less studied in oncology settings, where most patients are conscious and able to communicate almost until dying. The aim of this study was to explore oncologists' and nurses' perceptions of family involvement in decision making about forgoing cancer‐specific treatment in patients with advanced cancer. Materials and Methods: Qualitative semistructured interviews with 22 oncologists and 7 oncology nurses were analyzed according to the grounded theory approach. The results were discussed against the background of the clinical and ethical debate on family role near the end of life. Results: We could identify two approaches shared by both oncologists and nurses toward family involvement. These approaches could be partly explained by different perception and definition of the concept of patients' autonomy: (a) a patient‐focused approach in which a patient's independence in decision making was the highest priority for oncologists and (b) a mediator approach with a family focus in which oncologists and nurses assigned an active role to patients' family in decision making and strived for building consensus and resolving conflicts. Conclusion: The main challenge was to involve family, increasing their positive influences on the patient and avoiding a negative one. Thereby, the task of both oncologists and oncology nurses is to support a patient's family in understanding of a patient's incurable condition and to identify a patient's preference for therapy. Implications for Practice: This study focused on oncologists' and oncology nurses' perceptions of family involvement in decision making about treatment limitation in patients with advanced cancer who are able to communicate in a hospital setting. Oncologists and oncology nurses should be aware of both positive aspects and challenges of family involvement. Positive aspects are patients' emotional support and support in understanding and managing the information regarding treatment decisions. Challenges are diverging family preferences with regard to treatment goals that might become a barrier to advanced care planning, a possible increased psychological burden for the family. Especially challenging is involving the family of a young patient because increased attention, more time investment, and detailed discussions are needed. Abstract : The role of family communication is recognized as an important factor in decision making for cancer patients near the end of life. This article discusses the value and role of family in end‐of‐life discussions and the challenges encountered by oncologist and oncology nurses when involving family in decision making.